A synthesis method and application of heteroatom-doped phenolic resin microspheres
By covering heteroatom-doped carbon dots in phenolic resin microspheres and subjecting hydrothermal treatment to form a phenolic resin photocatalyst rich in quinone structure and fixed carbon dots, the problems of high synthesis conditions and limited catalytic performance of existing phenolic resin materials are solved, and efficient photocatalytic performance and material stability are achieved.
Patent Information
- Application Number
- CN202310489542.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-04
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-05-04
AI Technical Summary
The existing phenolic resin materials are synthesized under high temperature and high pressure conditions, and the catalytic performance is limited, making it difficult to further improve the photocatalytic performance.
By in situ coating heteroatom-doped carbon dots in the prepolymerization of phenolic resin microspheres and hydrothermal treatment under an oxygen-free condition, a heteroatom-doped phenolic resin photocatalyst rich in quinone structure and fixed carbon dots is formed.
It significantly improves the photocatalytic properties of phenolic resins, can efficiently catalyze the formation of hydrogen peroxide under mild conditions, and the material has the characteristics of environmentally friendly, suitable for large-scale preparation, chemical and thermal stability.
Smart Images

Figure CN116493047B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional materials, and in particular relates to a preparation method and application of a heteroatom-doped phenolic resin material. Background Art
[0002] As one of the most common chemicals, hydrogen peroxide is not only a green and efficient oxidant, but also an energy carrier that is easy to store. Anthraquinone oxidation is currently the main method for producing hydrogen peroxide, but it consumes a lot of energy, causes serious pollution, and does not meet the requirements of sustainable development. Solar-driven photocatalytic preparation of hydrogen peroxide is safe and environmentally friendly, and is a very promising development direction, among which the development of photocatalysts is its core content. Conjugated polymers are an important class of organic photocatalytic materials that have attracted much attention for their advantages such as adjustable structure, easy preparation, abundant raw materials, and no toxic metal elements. However, from the perspective of application development and large-scale production, the development of general polymer materials for photocatalysis has practical significance and use value.
[0003] The phenolic resin obtained by condensation of resorcinol and formaldehyde exhibits typical semiconductor properties, which is mainly attributed to the phenol and benzoquinone unit structures generated on the polymer skeleton, which play the role of electron donor and electron acceptor respectively, so that under light excitation, the separation efficiency of photogenerated electrons and holes is enhanced, and the reaction of visible light catalytic oxygen reduction to hydrogen peroxide under mild conditions is promoted. The content of quinone structure directly determines the photocatalytic performance of phenolic resin. However, on the one hand, such phenolic resin with photocatalytic activity needs to be synthesized in a hydrothermal reactor at high temperature and high pressure. With water and ethanol as solvents, the reaction temperature needs to reach 250℃, the internal pressure in the reactor is high, and the reaction time exceeds 24 hours. Therefore, it is urgent to explore a mild and effective synthesis route; on the other hand, although the donor-acceptor component can be increased in phenolic resin by converting the phenol structure into a quinone structure, the catalytic performance cannot be further improved due to the limited number of active sites. Therefore, it is necessary to introduce additional photocatalytic active sites to promote the application prospects of phenolic resin in the conversion of solar energy into chemical energy.
[0004] Introducing heteroatoms into organic semiconductor materials is one of the effective strategies to improve the photocatalytic performance of materials. Building blocks with heteroatoms such as nitrogen, sulfur, and phosphorus are designed and introduced into polymers through copolymerization or post-modification strategies. Doping can reduce the band gap and enhance the light absorption capacity by perturbing the hybrid orbital and regulating the band structure of the photocatalyst. In addition, element doping can also adjust the electronic structure to improve the charge separation efficiency. The strategy of doping different elements in phenolic resin is currently less developed. Compounding heteroatom-doped carbon dots into phenolic resin can not only improve the photocatalytic properties through heteroatoms, but also the carbon dots, as electron transfer agents, will further improve the transfer properties of photogenerated charges, thereby improving the photocatalytic activity of phenolic resin. Summary of the invention
[0005] In view of this, the object of the present invention is to provide a method for preparing heteroatom-doped phenolic resin microspheres with high catalytic activity and application thereof in photocatalytic preparation of hydrogen peroxide.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention explores the synthesis mechanism of phenolic resin and optimizes the synthesis route, proposes a new synthesis route, uses phenolic resin microspheres to pre-polymerize and coat heteroatom-doped carbon dots, studies the hydrothermal treatment of pre-polymerized microspheres under anaerobic conditions, and develops heteroatom-doped phenolic resin photocatalysts rich in quinone structure and fixed carbon dots.
[0008] The preparation method of heteroatom-doped phenolic resin microspheres proposed by the present invention comprises the following specific steps:
[0009] A two-step synthesis route of prepolymerization and hydrothermal treatment was adopted to in situ encapsulate heteroatom carbon dots in the prepolymerization reaction of resorcinol and formaldehyde, and then a heteroatom-doped phenolic resin photocatalyst was obtained through a hydrothermal reaction, which was denoted as RF@CD.
[0010] The specific process of preparation is:
[0011] Phenolic resin (RF) prepolymer microspheres coated with carbon dots were prepared by using a modified The method comprises adding 0.5-5wt% (compared to the amount of resorcinol) of carbon dot (CD) solution to a mixed solution of deionized water / anhydrous ethanol (v / v=2-2.5), using 100-200 μL of ammonia water as a catalyst, weighing 1.5-2.5 mmol of resorcinol and 0.2-0.4 mL of 37% formaldehyde solution, and prepolymerizing at room temperature for 10-12 hours. In a heat-resistant glass tube of a certain capacity, the prepolymer solution is added, and liquid nitrogen is used for freeze-thaw degassing 2-3 times, and then the glass tube is sealed and placed in an oven at 80°C-120°C for reaction for 5-8 hours; after the reaction is completed, the mixture is washed alternately with deionized water and anhydrous ethanol three times, and dried in a vacuum oven at 40°C to obtain the target product, namely the heteroatom-doped phenolic resin microspheres (RF@CD).
[0012] It should be noted that the prepolymer-coated carbon dots step is to coat the heteroatom carbon dots inside or on the surface of the phenolic resin microspheres while the microspheres are being formed in the reaction solution.
[0013] The hydrothermal treatment step is a process of increasing the quinone structure content in the phenolic resin microspheres and fixing the carbon points at a certain reaction temperature in an oxygen-free sealing system.
[0014] Optionally, the added carbon dots are heteroatom-doped carbon dots, and the carbon dots include nitrogen-containing carbon dots N-CD and nitrogen-containing sulfur carbon dots N,S-CD.
[0015] Furthermore, the present invention also seeks to protect the use of the heteroatom carbon dot composite phenolic resin prepared by the above method in the field of photocatalysis.
[0016] Specifically, the heteroatom carbon dot composite phenolic resin is used as a catalyst in the photocatalytic preparation of hydrogen peroxide; the specific operation steps are as follows:
[0017] Weigh 30-60 mg of heteroatom carbon dot composite phenolic resin as a photocatalyst, disperse it in 30-50 mL of pure water system, use a 300 W xenon lamp (λ>420 nm) as a light source, and carry out photocatalytic reaction under the condition of continuous introduction of oxygen. The temperature of the reaction system is maintained at room temperature. After the photocatalytic reaction is completed, collect the supernatant to test the production of hydrogen peroxide in the system.
[0018] It can be seen from the above technical solution that, compared with the prior art, the synthesis method and application of heteroatom-doped phenolic resin microspheres provided by the present invention have the following excellent effects:
[0019] 1) The present invention proposes a strategy to improve the photocatalytic activity of phenolic resin based on heteroatom carbon dots. In the prepolymerization of phenolic resin microspheres, carbon dots doped with different heteroatoms are in situ coated, and nitrogen and sulfur atoms are introduced into the phenolic resin to form a composite catalyst to delay the recombination of photogenerated electrons and holes. The experimental results show that the phenolic resin material after composite heteroatoms significantly delays the recombination of photogenerated electrons and holes in the absence of sacrificial agents, showing high photocatalytic performance, and can be used in the field of photocatalytic preparation of hydrogen peroxide, which promotes the application and development of phenolic resin microspheres in the field of solar energy conversion.
[0020] 2) The polymer material of the present invention uses low-cost resorcinol and formaldehyde as raw materials and adds heteroatom carbon dots for compounding. The method promotes the conversion of phenolic resin to form rich quinone structures and chemically fixes the pre-coated carbon dots in a hydrothermal reaction under anaerobic conditions, thereby forming heteroatom-doped phenolic resin microspheres. The functional material has the characteristics of environmental friendliness, suitability for large-scale preparation, chemical and thermal stability; in photocatalytic reactions, it has the characteristics of high catalytic efficiency, high selectivity, high recovery rate and reusability. The entire catalytic process has a simple operation flow, no pollution, no need to add sacrificial agents, and has good industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0022] Figure 1 This is the UV-visible absorption spectrum of the nitrogen-sulfur carbon dots (N,S-CD) prepared in the present invention.
[0023] Figure 2 This is the fluorescence spectrum of the nitrogen-sulfur carbon dots (N,S-CD) prepared in the present invention.
[0024] Figure 3 This is the TEM image of nitrogen-sulfur doped phenolic resin microspheres (RF@N,S-CD) prepared in the present invention.
[0025] Figure 4 Infrared spectra of RF, N,S-CD and RF@N,S-CD prepared in the present invention.
[0026] Figure 5 This is the ultraviolet absorption spectrum of nitrogen-sulfur doped phenolic resin microspheres (RF@N,S-CD) prepared in the present invention.
[0027] Figure 6 This is the MS curve of nitrogen-sulfur doped phenolic resin microspheres (RF@N,S-CD) prepared in the present invention.
[0028] Figure 7 The hydrogen peroxide production of RF and RF@N,S-CD at different catalytic times.
[0029] Figure 8 This study tests the cyclic stability of nitrogen-sulfur doped phenolic resin microspheres (RF@N,S-CD) for photocatalytic production of hydrogen peroxide. DETAILED DESCRIPTION
[0030] The following will be combined with the embodiments of the present invention and the drawings of the specification to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The embodiment of the invention discloses a method for synthesizing heteroatom-doped phenolic resin microspheres.
[0032] In order to better understand the present invention, the present invention is further specifically described below through the following examples, but it should not be understood as a limitation of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above invention content are also considered to fall within the protection scope of the present invention.
[0033] The technical solution of the present invention will be further described below in conjunction with specific embodiments.
[0034] Example 1: Preparation of nitrogen-sulfur carbon dots (N,S-CD):
[0035] Nitrogen-sulfur carbon dots (N,S-CD) were synthesized by one-step hydrothermal treatment, in which citric acid (CA) was used as the carbon source and L-cysteine provided nitrogen and sulfur atoms.
[0036] Weigh 2g of citric acid (CA) and 1g of L-cysteine and dissolve them in 5mL of water. Evaporate at 70℃ for 12 hours to obtain a viscous product. Add it into a hydrothermal reactor and react at 200℃ for 3 hours. After the reaction is completed, use 1mol·L -1 Neutralize with NaOH solution and dilute to 100 mL.
[0037] The UV-visible absorption spectrum of the nitrogen-sulfur carbon dots (N,S-CD) prepared in this example is mainly concentrated in the ultraviolet region ( Figure 1 ), there is an obvious absorption peak at 350nm. At an excitation wavelength of 360nm, the emission peak of N,S-CD is located at 475nm, and bright blue fluorescence is observed under ultraviolet laser irradiation ( Figure 2 ).
[0038] Example 2: Preparation of Nitrogen-Sulfur Doped Phenolic Resin Microspheres (RF@N,S-CD):
[0039] A 0.5-5 wt% (compared to the amount of resorcinol) nitrogen-sulfur carbon dot (N, S-CD) solution was added to a mixed solution of deionized water / anhydrous ethanol (v / v = 2-2.5), 100-200 μL of ammonia water was used as a catalyst, 1.5 mmol-2.5 mmol of resorcinol and 0.2 mL-0.4 mL of 37% formaldehyde solution were weighed and stirred for prepolymerization for 10-12 hours. Then, the prepolymer solution was added to a heat-resistant glass tube of a certain capacity, and liquid nitrogen was used for freeze-thaw degassing 2-3 times, and then the glass tube was sealed and placed in an oven at 80°C-120°C for reaction for 5-8 hours. After the reaction was completed, it was washed alternately with deionized water and anhydrous ethanol three times, and dried in a vacuum oven at 40°C to obtain the target nitrogen-sulfur doped phenolic resin microspheres (RF@N, S-CD). Among them, the effects of different synthesis parameters on the RF photocatalytic performance are shown in Table 3.
[0040] Embodiment 3:
[0041] Add 5 mg of nitrogen-sulfur carbon dots (N, S-CD) solution to a mixed solution of deionized water / anhydrous ethanol (20 mL / 8 mL), add 100 μL of ammonia water as a catalyst, weigh 200 mg of resorcinol and add 0.28 mL of 37% formaldehyde solution to stir for prepolymerization. Then, add the previous prepolymer solution to a heat-resistant glass tube of a certain capacity, freeze-thaw and degas with liquid nitrogen three times, then seal the glass tube and place it in a 100 ° C oven for 6 hours. After the reaction, wash it alternately with deionized water and anhydrous ethanol three times, and dry it in a vacuum oven at 40 ° C to obtain the target nitrogen-sulfur doped phenolic resin microspheres (RF@N, S-CD).
[0042] TEM image of nitrogen-sulfur doped phenolic resin microspheres (RF@N,S-CD) prepared in Example 3 ( Figure 3 ) showed that the RF@N,S-CD samples were spherical and monodisperse, with particle sizes ranging from 600 to 800 nm. After hydrothermal treatment, the resin microspheres showed a certain degree of fusion.
[0043] The infrared spectrum of the RF@N,S-CD sample prepared in Example 3 ( Figure 4 ) at 2600cm -1 The characteristic peak of sulfur bond (-SH) appears at , indicating that the carbon dots are in situ coated inside or on the surface of phenolic resin microspheres during the prepolymerization step.
[0044] The composite heteroatom RF microspheres prepared in Example 3 have a wide absorption in the visible light region, with a maximum absorption wavelength of around 525 nm ( Figure 5 ). The optical band gap Eg (2.06 eV) of the material was calculated by the formula, which is smaller than that of the blank RF resin microspheres (2.17 eV).
[0045] The heteroatom-doped phenolic resin microspheres prepared in Example 3 were subjected to MS test ( Figure 6 ), a tangent is drawn to the longest straight line of the MS curve, and the slope of the tangent is positive, indicating that the RF microspheres after composite carbon dots are still n-type semiconductors. The conduction band potential of the semiconductor is inferred based on the flat band potential value, and the energy level structure of the semiconductor is determined by combining the bandgap width Eg obtained by UV-vis. Since the photocatalytic production of hydrogen peroxide by RF resin microspheres is mainly promoted by two half reactions of oxygen reduction and water oxidation, among which the water oxidation half reaction requires a larger overpotential and is the rate-determining step of the entire photocatalytic reaction, it is necessary to pay attention to the change in the valence band position of the composite material in the comparison of the energy band structure. Compared with blank RF resin microspheres, CD doped with N,S can make the valence band potential of RF resin microspheres positively shift to 1.76eV (Table 2), obtaining stronger oxidation ability.
[0046] In addition, the inventors also used the prepared heteroatom-doped phenolic resin microspheres for photocatalytic preparation of hydrogen peroxide, and the specific operation is as follows:
[0047] 30-60 mg of the heteroatom-doped phenolic resin microspheres prepared in Example 3 were weighed as photocatalysts and dispersed in 30-50 mL of pure water. A 300 W xenon lamp (λ>420 nm) was used as a light source to induce photocatalytic production of hydrogen peroxide under the condition of continuous introduction of oxygen, and the temperature of the reaction system was always kept at room temperature. After the photocatalytic reaction was completed, the supernatant was collected by centrifugation to measure the content of hydrogen peroxide generated by the system.
[0048] In this experiment, the photocatalytic performance of the composite resin with different carbon dot dosages under λ>420nm is shown in Table 1. The carbon dot dosage increases from 0.1mg, 0.5mg, 2mg, 5mg to 8mg. With the increase of N,S-CD dosage, the photocatalytic hydrogen peroxide generation of the composite material also gradually increases. When the carbon dot dosage increases to 5mg, the hydrogen peroxide production reaches a peak value, that is, the hydrogen peroxide production catalyzed by visible light in 8 hours is 36.1μmol. Further increase the carbon dot dosage, the hydrogen peroxide production begins to decrease. The phenolic resin also shows the same photocatalytic activity, and the hydrogen peroxide production catalyzed by visible light in 8 hours is 24.2μmol. Therefore, the phenolic resin composited with N,S-CD shows better photocatalytic performance.
[0049] The composite samples with the best performance were selected for cyclic stability test ( Figure 8 ), the photocatalytic rate in the first four-hour cycle can reach 135 μmol g -1 h -1 After 3 cycles of 12 hours, the production of hydrogen peroxide decreased from 27.0 μmol to 24.5 μmol, indicating that the composite material after RF doping N,S-CD still maintains good cycle stability.
[0050] The cumulative hydrogen peroxide production of the system after 12 hours and 24 hours of photocatalysis of RF@N,S-CD was 48.0 μmol and 72.3 μmol, respectively, which was significantly higher than the performance of the blank RF resin ( Figure 7 ).
[0051] Table 1 The content of hydrogen peroxide produced by the composite resin catalyzed by different carbon dot dosages at λ>420nm.
[0052]
[0053] a Photocatalytic conditions: 50 mg sample, 30 mL H2O (without adding sacrificial agent), catalytic time 8 h.
[0054] Table 2 Band positions of RF@N, S-CD and RF.
[0055]
[0056]
[0057] Table 3 Effect of different synthesis parameters on RF photocatalytic performance
[0058]
[0059] a Photocatalytic conditions: 50 mg sample, 30 mL H2O (without adding sacrificial agent), catalytic time 8 h.
[0060] It can be seen from the above embodiments that the present invention provides a method for preparing phenolic resin microspheres with photocatalytic activity. A two-step method is used to achieve functional doping. Low-cost, commercial resorcinol and formaldehyde are used as raw materials. Carbon dots doped with different heteroatoms are in situ coated in the prepolymerization of phenolic resin microspheres. Further, in a hydrothermal reaction under anaerobic conditions, the phenolic resin is promoted to convert into a rich quinone structure and the pre-coated carbon dots are chemically fixed, thereby forming heteroatom-doped phenolic resin microspheres. Among them, S, N-doped CDs contribute more to the positive shift of the valence band. After modification, the oxidation capacity of the holes in the sample is gradually enhanced, which can significantly promote the process of water oxidation.
[0061] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a heteroatom carbon point composite phenolic resin, characterized in that: Using resorcinol, formaldehyde, and carbon dots doped with different heteroatoms as raw materials, heteroatom-doped phenolic resin microspheres were prepared by prepolymerization, coating, and mild hydrothermal treatment, denoted as RF@CD. The method specifically comprises the following steps: 1) Add carbon dots (CD) solution to a mixed solution of deionized water / anhydrous ethanol, use ammonia water as a catalyst, weigh resorcinol and 37% formaldehyde solution, stir and prepolymerize at room temperature for 10-12 hours; 2) Add the prepolymer solution prepared in step 1) to a heat-resistant glass tube, freeze-thaw and degas using liquid nitrogen for 2 to 3 times, then seal the glass tube and place it at 80 o C ~ 120 o After the reaction is completed, the mixture is washed with deionized water and anhydrous ethanol three times in a vacuum oven at 40 o C and dried to obtain the target product, i.e., the heteroatom-doped phenolic resin microspheres.
2. The method for preparing the heteroatom carbon dot composite phenolic resin according to claim 1, characterized in that: The volume ratio of deionized water to anhydrous ethanol in the mixed solution is (2-2.5):1, the mass percentage of the carbon dots to resorcinol is 0.5~5wt%, the volume ratio of ammonia water to 37% formaldehyde solution is 100~200 μL: 0.2 mL ~ 0.4 mL, and the amount of resorcinol is 1.5 mmol ~ 2.5 mmol.
3. The method for preparing the heteroatom carbon dot composite phenolic resin according to claim 1, characterized in that: The added carbon dots are heteroatom-doped carbon dots, and the carbon dots include nitrogen-containing carbon dots N-CD and nitrogen-containing sulfur carbon dots N,S-CD.
4. Use of the heteroatom carbon dot composite phenolic resin prepared by the method according to any one of claims 1 to 3 in the field of photocatalysis.
5. The use according to claim 4, characterized in that: The heteroatom carbon dot composite phenolic resin is used as a catalyst in the photocatalytic preparation of hydrogen peroxide; the specific operation steps are as follows: 30 ~ 60 mg of heteroatom carbon dot composite phenolic resin was weighed as a photocatalyst and dispersed in 30 ~ 50 mL of pure water system. A 300 W xenon lamp (λ > 420 nm) was used as the light source. The photocatalytic reaction was carried out under the condition of continuous oxygen introduction. The temperature of the reaction system was maintained at room temperature. After the photocatalytic reaction was completed, the supernatant was collected to test the hydrogen peroxide production in the system.